Rubber composition and its uses
Patent Information
- Application Number
- JP2021050819
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-24
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-03-24
AI Technical Summary
【0013】 本発明によれば、ポリロタキサンを含むゴム組成物及びその利用物において、水分子が混入しにくくなり、加水分解反応等の発生及び絶縁性能の低下が抑制され、耐湿性が向上するという優れた効果を奏する。
Smart Images

Figure 0007633056000003 
Figure 0007633056000004 
Figure 0007633056000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a rubber composition containing polyrotaxane and to applications thereof, such as dielectric sheets, sensors, and actuators. [Background technology]
[0002] Polyrotaxane is a molecular assembly in which linear molecules penetrate cyclic molecules so that they can slide relative to one another, and the cyclic molecules are prevented from detaching due to blocking groups at both ends of the linear molecules, and is called a slide-ring material. Various types of cyclic molecules and linear molecules are known, but cyclodextrin is often used as the cyclic molecule and polyethylene glycol as the linear molecule (Patent Documents 1 and 2).
[0003] Furthermore, crosslinked polyrotaxanes obtained by crosslinking polyrotaxanes are expected to be used as materials for actuators and the like because of their high dielectric constant and unique mechanical properties such as viscoelasticity (Patent Document 3).
[0004] However, because actuators are used under high-voltage conditions, the insulation performance is likely to decrease if air bubbles or water molecules with different dielectric constants are mixed into the dielectric layer material. In particular, because cyclodextrin and polyethylene glycol have high water absorption, forming a dielectric layer using crosslinked polyrotaxane containing them reduces moisture resistance, and there is a problem that the insulation performance decreases due to hydrolysis reactions, etc.
[0005] The present applicant has proposed a crosslinked polyrotaxane that is blended with a block polymer containing polysiloxane to make it less susceptible to inclusion of water molecules and improve moisture resistance (Patent Document 4), but there is still room for improvement. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2005 / 080469 [Patent Document 2] International Publication No. 2008 / 108411 [Patent Document 3] JP 2011-241401 A [Patent Document 4] JP 2017-066318 A Summary of the Invention [Problem to be solved by the invention]
[0007] Therefore, an object of the present invention is to make it difficult for water molecules to be mixed into a rubber composition containing polyrotaxane and an article using the same, thereby suppressing the occurrence of hydrolysis reactions and the like and deterioration of insulating performance, and improving moisture resistance. [Means for solving the problem]
[0008] [1] Rubber composition A rubber composition obtained by urethane crosslinking of a diene rubber having a hydroxyl group and a polyrotaxane which is a cyclodextrin whose cyclic molecules are modified with a hydrocarbon, using an isocyanate as a crosslinking agent.
[0009] [Effect] Polyrotaxane became miscible with diene rubber only after its cyclic molecule, cyclodextrin, was modified with hydrocarbons. As a result, in rubber compositions containing polyrotaxane, the hydrophobicity of diene rubber makes it difficult for water molecules to be mixed in, suppressing the occurrence of hydrolysis reactions and the deterioration of insulation performance, thereby improving moisture resistance.
[0010] [2] Dielectric sheet A dielectric sheet comprising the rubber composition of [1] above.
[0011] [3] Actuator An actuator that uses the dielectric sheet mentioned above [2].
[0012] [4] Sensor A sensor using the dielectric sheet mentioned above [2]. Effect of the Invention
[0013] According to the present invention, in a rubber composition containing polyrotaxane and an article using the same, the excellent effects of making it difficult for water molecules to be mixed in, suppressing the occurrence of hydrolysis reactions and the like and the deterioration of insulating performance, and improving moisture resistance are achieved. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1(a) is a diagram showing a schematic structure of the crosslinked body (rubber composition) of Example 1, and (b) is a diagram showing a schematic structure of the crosslinked body of Comparative Example 1. [Diagram 2] FIG. 2 is an explanatory diagram of a method for measuring the dielectric breakdown voltage. [Diagram 3] FIG. 3 is a cross-sectional view of an actuator (or sensor) produced using the crosslinked product (rubber composition) of the example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] (1) Diene rubber having hydroxyl groups Examples of diene rubbers include, but are not limited to, butadiene rubber (BR), styrene-butadiene rubber (SBR), isoprene rubber (IR), chloroprene rubber (CR), and acrylonitrile-butadiene rubber (NBR). The hydroxyl group may be present at the molecular terminal of the diene rubber or may be present by grafting.
[0016] (2) Polyrotaxane, a cyclic molecule of a hydrocarbon-modified cyclodextrin Examples of cyclodextrin include α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin. Examples of the hydrocarbon modification of cyclodextrin include an alkyl group modification and an aryl group modification.
[0017] Examples of linear polyrotaxane molecules include, but are not limited to, polyethylene glycol (PEG), polypropylene glycol (PPG), polylactic acid, polyisoprene, polyisobutylene, polybutadiene, polytetrahydrofuran, polydimethylsiloxane, polyethylene, polypropylene, polyvinyl alcohol, and polyvinyl methyl ether.
[0018] The blocking group of the polyrotaxane is not particularly limited, and examples thereof include dinitrophenyl groups, cyclodextrins, adamantane groups, trityl groups, fluoresceins, pyrenes, substituted benzenes (substituents include alkyl, alkyloxy, hydroxy, halogen, cyano, sulfonyl, carboxyl, amino, phenyl, etc., and one or more substituents may be present), optionally substituted polynuclear aromatics (substituents include the same as those described above, and one or more substituents may be present), and steroids. It is preferably selected from the group consisting of dinitrophenyl groups, cyclodextrins, adamantane groups, trityl groups, fluoresceins, and pyrenes, and more preferably adamantane groups or trityl groups.
[0019] (3) Isocyanate The isocyanate is not particularly limited, but examples thereof include diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), tolylene diisocyanate (TDI), methyl isocyanate (MIC), polyfunctional isocyanates, aromatic polyfunctional isocyanates, and the like.
[0020] (4) Dielectric sheet The dielectric breakdown voltage of the dielectric sheet (at normal temperature and humidity) was 72V / μm after it was placed in an environment with a temperature of 60°C and a relative humidity of 90% for one hour. End is preferable, because this provides satisfactory moisture resistance under high humidity conditions. EXAMPLES
[0021] Rubber compositions of Examples 1 and 2 and Comparative Examples 1 and 2 shown in Table 1 were prepared and their properties were measured. The units of compounding values in Table 1 are: <4> As will be described later, (g).
[0022] [Table 1]
[0023] The details of the examples and comparative examples will be described in the following order: It should be noted that the present invention is not limited to these examples. <1> Polyrotaxane <2> Crosslinking Agent <3> polymer <4> Preparation of crosslinked body (rubber composition) <5> Measurement of characteristics <6> Fabrication of actuators (or sensors)
[0024] <1> Polyrotaxane <1-1> Example: Synthesis of hydrocarbon-modified polyrotaxane First, an adamantane polyrotaxane (APR) consisting of a linear molecule: PEG (average molecular weight: 35,000), a cyclic molecule: α-cyclodextrin, and a blocking group: adamantane group was prepared by the method described in International Publication No. 2008 / 108411 (Patent Document 2). Next, the prepared APR was modified with hydroxypropyl groups to prepare hydroxypropylated polyrotaxane (HAPR) by the method described in Patent Document 2. The weight-average molecular weight Mw of the prepared HAPR was measured by gel permeation chromatography (GPC) and found to be 120,000. Nuclear magnetic resonance (NMR) analysis also showed that 48% of the hydroxyl groups of cyclodextrin were replaced with hydroxypropyl. Next, 10 g of the prepared HAPR and 40 ml of dimethylacetamide were added to the reactor to dissolve, and 6 ml of triethylamine was added while stirring. 9.6 ml of myristic acid chloride was slowly added dropwise while cooling the reaction vessel with water, and the reaction was continued for 15 hours. The obtained solution was reprecipitated in deionized water, and the solid was washed several times with deionized water and then dried under reduced pressure in a dryer at 80 ° C. 54.0 g of toluene was added to the obtained viscous solid 13.5 g to dissolve it, and 67.5 g of a hydrocarbon-modified polyrotaxane solution (solid content 20 wt % solution) having myristic acid ester groups on α-cyclodextrin, a cyclic molecule, was obtained. The resulting hydrocarbon-modified polyrotaxane was analyzed by GPC and found to have a weight average molecular weight (Mw) of 251,000, and a hydroxyl value of 19.1 mgKOH / g.
[0025] <1-2> Comparative Example 1: Synthesis of HAPR-g-PCL First, we prepared a hydroxypropyl-modified polyrotaxane (HAPR) disclosed in International Publication No. 2005 / 080469 (Patent Document 1), which is a polyrotaxane containing cyclodextrin in the cyclic molecule, PEG in the linear molecule, and having blocking groups at both ends of the linear molecule. Next, in order to obtain solubility and compatibility, polyrotaxane having a caprolactone group was prepared by the following method. 10 g of the above HAPR was placed in a three-neck flask, and 45 g of ε-caprolactone was introduced while slowly flowing nitrogen. After uniform stirring at 100°C for 30 minutes with a mechanical stirrer, the reaction temperature was raised to 130°C, 0.32 g of tin 2-ethylhexanoate (50 wt% solution) previously diluted with toluene was added, and the reaction was carried out for 5 hours, and the solvent was removed to obtain 55 g of polyrotaxane having a caprolactone group (HAPR-g-PCL). The obtained HAPR-g-PCL was analyzed by GPC, and the weight average molecular weight Mw was 580,000 and the molecular weight distribution Mw / Mn was 1.5.
[0026] <2> Crosslinking Agent <2-1> Polymeric MDI A polymeric MDI manufactured by Tosoh Corporation, trade name "Millionate MR200", was used.
[0027] <2-2> HDI polyisocyanate HDI-based polyisocyanate manufactured by Asahi Kasei Corporation, trade name "Duranate SBL-100" was used.
[0028] <2-3> Preparation of PPG with end-blocked isocyanate groups PPG700, diol type (500 g, Fujifilm Wako Pure Chemical Industries, Ltd.), and Plaxel M (430 g, Daicel Corporation), a monomer of ε-caprolactone, were added to a three-necked flask, and the mixture was stirred for 2 hours under a nitrogen stream in an oil bath at 110°C. After the oil bath was heated to 130°C, tin 2-ethylhexanoate (0.5 g, Aldrich Corporation) was added and stirred for 10 hours to obtain PPG (oligomer 1) with polycaprolactone grafted to both ends. The above-mentioned Oligomer 1 (100 g) was added to a three-necked recovery flask, and then the mixture was stirred under a nitrogen stream in an oil bath at 90° C. Takenate 600 (7.45 g, manufactured by Mitsui Chemicals, Inc.) was slowly added dropwise to the solution over 1 hour, and the mixture was further stirred for 2 hours to obtain Oligomer 2. Takenate 600 (16.66 g) was added to a three-necked eggplant flask, and the mixture was stirred in a nitrogen stream in an oil bath at 90°C. A solution of the above-mentioned oligomer 2 (80 g) dissolved in toluene (80 g) was slowly added dropwise to this solution over a period of 2 hours, and the mixture was stirred for another 2 hours. After the reaction, the liquid temperature was lowered to 40°C, and then 2-butanone oxime (10.95 g, Tokyo Chemical Industry Co., Ltd.) was slowly added dropwise so that the liquid temperature did not exceed 60°C. After the addition, the mixture was stirred at 40°C for 5 hours to obtain a crosslinking agent solution containing PPG (PPG3200) having terminal blocked isocyanate groups (Mn: 5422).
[0029] <3> polymer <3-1> Hydroxyl-terminated liquid polybutadiene A hydroxyl-terminated liquid polybutadiene represented by the following chemical formula 1 (product name: "Poly bd R-15HT") manufactured by Idemitsu Kosan Co., Ltd. was used. [ka] <3-2>PPG700 diol The above-mentioned PPG700, diol type (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used. <3-3> PPG monool Poly(propylene glycol) monobutyl ether (Mn: 1000) (Sigma-Aldrich) was used.
[0030] <4> Preparation of crosslinked body (rubber composition) <4-1> Preparation of Example 1 A crosslinker solution containing 3.95 g of the hydrocarbon-modified polyrotaxane obtained in <1-1> above, 1.94 g of the crosslinker (Millionate MR200) in <2-1> above, and 8.74 g of the polymer (Poly bd R-15HT) in <3-1> above was dissolved in a solvent and stirred to obtain a homogeneous solution. To this solution, 0.24 g of antioxidant, 0.2 g of silicone additive (a solution prepared by dissolving DBL-C31 (manufactured by Gelest) in toluene to adjust the solid content to 30 wt%), and 0.41 g of Carbodilite V-09GB solution were added and stirred to obtain a homogeneous solution. The resulting solution was degassed and then molded into a sheet. The molded sample was processed into a crosslinked product (elastomer) under high temperature conditions under reduced pressure. The structure of the resulting crosslinked product (rubber composition) is shown diagrammatically in FIG. 1(a).
[0031] <4-2> Preparation of Example 2 A crosslinker solution containing 6.21 g of the hydrocarbon-modified polyrotaxane obtained in <1-1> above, 8.01 g of the crosslinker (Duranate SBL-100) in <2-2> above, and 13.77 g of the polymer (Poly bd R-15HT) in <3-1> above was dissolved in a solvent and stirred to obtain a homogeneous solution. To this solution, 0.49 g of antioxidant, 0.41 g of the silicone additive, and 0.81 g of Carbodilite V-09GB solution were added and stirred to obtain a homogeneous solution. The resulting solution was degassed and then molded into a sheet. The molded sample was processed into a crosslinked body (elastomer) under high temperature conditions under reduced pressure.
[0032] <4-3> Preparation of Comparative Example 1 10.9 g of HAPR-g-PCL obtained in <1-2> above and 27.3 g of the crosslinker solution containing the crosslinker (PPG3200) obtained in <2-3> above were dissolved in a solvent and stirred to obtain a homogeneous solution. To this solution, 0.8g of dibutyltin dilaurate solution (3wt%), 0.8g of silicon additive, 1.6g of hydrolysis inhibitor, and 1.0g of antioxidant were added and stirred to obtain a homogeneous solution. The resulting solution was degassed and then molded into a sheet. The molded sample was processed into a crosslinked body (elastomer) under high temperature conditions under reduced pressure. The structure of the obtained crosslinked product is shown diagrammatically in FIG. 1(b).
[0033] <4-4> Comparative Example 2 The evaluation was carried out using a silicone elastomer film manufactured by WACKER: product name "ELASTOSIL Film 2030" (thickness 50 μm).
[0034] <5> Measurement of characteristics The following characteristics were measured for Examples 1 and 2 and Comparative Examples 1 and 2. The measurement results are shown in Table 1. <5-1>Initial elastic modulus The crosslinked body was cut into a dumbbell-shaped No. 7 specimen in accordance with JIS K-6251 to prepare a measurement specimen. For each specimen, a stress-displacement (elongation) curve was measured using an autograph AGS-5kNX manufactured by Shimadzu Corporation, with an effective tensile length of 20 mm and a tensile speed of 100 mm / min. The initial elastic modulus was calculated from the slope of a linear approximation of the stress-strain curve from 1 to 5% elongation.
[0035] All of Examples 1 and 2 and Comparative Examples 1 and 2 satisfied the target value of 1 to 3 MPa for the initial elastic modulus.
[0036] <5-2> Hysteresis loss As in Patent Document 3, hysteresis loss refers to the rate of mechanical energy loss (hysteresis loss) in one cycle of deformation and recovery in accordance with JIS K6400, where the strain obtained by a tensile test of the material is used instead of the deformation of the material. Specifically, a dumbbell No. 7 sample (dumbbell No. 7 conforms to JIS K-6251) is subjected to a tensile test to measure a stress-strain curve. After elongation to 100% of the effective length, it is contracted to 0% at the same speed as the elongation. This cycle is repeated 10 times, and the average value from the second to the tenth cycle is calculated as the hysteresis loss using the method of measuring and calculating the area described in Patent Document 3.
[0037] All of Examples 1 and 2 and Comparative Examples 1 and 2 satisfied the target value of 10% or less for the hysteresis loss.
[0038] <5-3> Dielectric constant Platinum was evaporated onto each sample to an inner diameter of 5 mm using a JEOL Auto Fine Coater "JEC-3000FC," and the capacitance was measured using an Agilent "4294A Precision Impedance Analyzer" with a dielectric constant measurement probe to calculate the relative dielectric constant.
[0039] The target value of the relative dielectric constant of 4 or more was satisfied in Examples 1 and 2 and Comparative Example 1, but not in Comparative Example 2.
[0040] <5-4> Dielectric breakdown voltage (dielectric breakdown field strength) First, the initial crosslinked body thickness within 48 hours after preparation was measured. Next, as shown in FIG. 2, the initial crosslinked body 1 was attached to the disk electrode 21 on the installation side, and the cylindrical electrode 22 was placed on the crosslinked body 1, with attention paid to leaving as few air bubbles as possible between the crosslinked body 1 and each electrode 21, 22, and further degassing was performed using a vacuum device. This was set in an insulation breakdown measuring device at room temperature and normal humidity, and a voltage was applied between the electrodes 21, 22 by the power supply device 23 at a voltage rise rate of 10 V / 0.1 seconds. Then, after passing through an insulation state in which no current flows substantially, the insulation breakdown voltage (V / μm) was calculated from the voltage at the point when the current became 1.2 μA or more. The normal temperature is 20±15°C, and the normal humidity is 65±20% (JIS-8703). Next, the crosslinked body was placed in a high humidity environment at a temperature of 60° C. and a relative humidity (RH) of 90% for 1 hour, and then the dielectric breakdown voltage was measured at normal temperature and humidity in the same manner as above.
[0041] Although Examples 1 and 2 and Comparative Example 2 satisfied the target value of the initial dielectric breakdown voltage of 72 V / μm or more, Comparative Example 1 did not. The target value of 72 V / μm or more for the dielectric breakdown voltage after keeping at high humidity was satisfied in Examples 1 and 2 and Comparative Example 2, but not in Comparative Example 1.
[0042] <5-5>Volume resistance A gold electrode was attached to the crosslinked body by sputtering. A fluorine-based inert liquid was dripped onto the metal surface of the shielding box, and the crosslinked body attached to the resin frame was set. A guard electrode was set on the surface of the crosslinked body, a positioning jig was set on the guard electrode, and the volume resistance (Ω / mm) was measured using a microcurrent meter.
[0043] Although Examples 1 and 2 and Comparative Example 2 satisfied the target volume resistivity value of 4E+12 or more, Comparative Example 1 did not.
[0044] <6> Fabrication of actuators (or sensors) The sheet-like crosslinked body 1 of the embodiment can be used as a dielectric sheet, and the crosslinked body 1 of the embodiment and the electrode layer 2 can be laminated alternately and then bonded by pressure bonding to produce an actuator 10, as shown in Fig. 3. The electrode layers 2 are composed of a group in which every other electrode layer is shifted to one side in the left-right direction, and a group in which every other electrode layer is shifted to the other side in the left-right direction. When a DC voltage is applied to one group as a positive electrode and the other group as a negative electrode, the crosslinked body 1 contracts in the film thickness direction, and the change in the total height of the actuator 10 due to the contraction can be used as a driving displacement. Similarly, a sensor can be produced by alternately laminating the bridged bodies 1 and the electrode layers 2.
[0045] The present invention is not limited to the above-described embodiment, and can be embodied by making appropriate modifications without departing from the spirit of the invention. [Explanation of symbols]
[0046] 1 Crosslinked product 2 electrode layer 10 Actuator 21 Disk electrode 22 Cylindrical electrode 23 Power supply
Claims
1. A rubber composition obtained by urethane crosslinking of a diene rubber having a hydroxyl group and a polyrotaxane which is a cyclodextrin whose cyclic molecules are modified with a hydrocarbon, using an isocyanate as a crosslinking agent.
2. A dielectric sheet comprising the rubber composition according to claim 1.
3. 3. The dielectric sheet according to claim 2, wherein the dielectric breakdown voltage (at normal temperature and humidity) of the dielectric sheet after being left for one hour in an environment having a temperature of 60° C. and a relative humidity of 90% is 72 V / μm or more.
4. An actuator using the dielectric sheet according to claim 2 or 3.
5. A sensor using the dielectric sheet according to claim 2 or 3.
Citation Information
Patent Citations
Polyurethane-elastomer actuator
JP1996335726A
Polyurethane elastomer-based actuator
JP2001294642A
Polyurethane elastomer actuator
JP2010233429A
Material having crosslinked polyrotaxane, and production method thereof
JP2011241401A
Rubber composition for tire and pneumatic tire employing the same
JP2014034621A